FURTHER MEASUREMENTS ON THE TL0.5PB0.5SR2(CA1-YYY)CU2O7-DELTA SYSTEM PB NMR AND MAGNETIC-SUSCEPTIBILITY - Dai, G; Tunstall, D; Dalton, M; Liu, R; Edwards, P (1995)
Susceptibility data are presented for the septenary alloy system Tl0.5Pb0.5Sr2(Ca1-yYy)Cu2O7-δ (0≤y≤0.5), together with Pb NMR. The earlier hypothesis that over the metallic alloy range at room temperature the spin susceptibility might be constant is shown to be incorrect. In correlating these new data with earlier copper and yttrium NMR data a consistent picture emerges of a one-component systems, but with a small (∼10%) anisotropy of the spin susceptibility of the copper planes. We show also that there is 89Y p character admixed into the copper hole wavefunctions. The susceptibility shows a pre-cursor drop in all samples at temperatures close to 120 K, well above Tc, perhaps an indication of spin pairing well into the non-superconducting region. This may be spin-fluctuation diamagnetism. © 1995.